PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT TANAH JAWA - Lasma Rohani Rosalia Samosir; Darwin Lie; Efendi Efendi; Fitria Halim (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The purpose of this study are: 1. To determine description of leadership’s style, work environment and employee performance at Kantor Camat Tanah Jawa. 2. To determine the influence of leadership’s style and work environment to employee performance at the Kantor Camat Tanah Jawa of simultaneouly or partially.The results of this study can be summarized as follows: 1. The leadership’s style is excellent, work environment is excellent and the performance of employees is excellent. 2. The results of regression analysis is Ŷ= 9,721 + 1,703X1 + 1,143X2, means that leadership’s style and work environment has a positive effect to employee performance 3. The results of the analysis correlations is r = 0,786, means that there is a moderately high corelation between leadership’s style and work environment to the performance of employees. The level of employee performance can be explained by leadership’s style and work environment as  61,8%. 4. The results of testing the hypothesis H0 is rejected, it means that leadership’s style and work environment has a positive effect and significant to the performance of employees at Kantor Camat Tanah Jawa of simultaneous or partialy. Keywords: Leadership Style, Work Environment And The performance Of Employees.